Pandangan Tokoh Arjuna Terhadap Stereotip Perempuan dalam Novel Populer Perempuan Bernama Arjuna Karya Remy Sylado - Nadia Karima (Program Studi Magister Linguistik Terapan UNJ, 2022)
This study aims to describe the image and stereotype of Indonesian women and the resistance ofthe character Arjuna in the popular novel Perempuan Bernama Arjuna against the image andstereotype that is widely developed. Arjuna is an Indonesian woman, father of a Chinese descentand mother who has thick Javanese blood. Arjuna, who is 25 years old, is a philosophy student ata university in the Netherlands. The method used in this research is descriptive analytic methodusing literature review technique. The data source used is the novel Perempuan Bernama Arjunaby Remy Sylado. The results of this study indicate that in the novel Perempuan Bernama Arjuna,there are 13 stereotypes of women. Of the 13 stereotypes of women that emerged, there were 10stereotypes that Arjuna refuted and considered not really representative of what womenexperienced, including himself, for example regarding women whose beauty is only judged fromtheir physical appearance. For him, the beauty of women is not only seen from the physical,more than that, women can also be judged from their intellectual level. There will be no use if awoman is physically beautiful, but does not have a qualified level of intelligence. In addition,there are 3 stereotypes of women whose existence Arjuna agrees with is also attached to him, forexample about women who are not used to speaking frankly as is in their hearts and heads.Arjuna who was educated by a mother who came from the Javanese tribe also adheres to onething taught by his mother, namely that a woman must be good at watching hermouth.